2007
DOI: 10.1007/s11244-007-9005-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production Via CH4 and CO Assisted Steam Electrolysis

Abstract: Porous composite anodes consisting of a yttria-stabilized zirconia (YSZ) backbone that was impregnated with CeO 2 and various amounts of metallic components including Cu, Co and Pd were fabricated. The performance of these anodes was then tested in a solid oxide water electrolysis cell under conditions where the anode was exposed to the reducing gasses H 2 , CH 4 and CO. The reducing gasses were used to decrease the electrochemical potential of the cell and increase overall efficiency. The results of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Where a cell is capable of being used as both fuel cell and as an electrolyser cell it is referred to as a solid oxide regenerative fuel cell (SORFC). Other applications apart from water electrolysis include CO 2 electrolysis, co-electrolysis of steam and CO 2 , or natural gas-assisted electrolysis [3,4,5,6]. The state of the art in SOEC for YSZ based cells using Ni-YSZ as the hydrogen electrode and LSM (or LSM-YSZ) as the oxygen electrode has been relatively active in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Where a cell is capable of being used as both fuel cell and as an electrolyser cell it is referred to as a solid oxide regenerative fuel cell (SORFC). Other applications apart from water electrolysis include CO 2 electrolysis, co-electrolysis of steam and CO 2 , or natural gas-assisted electrolysis [3,4,5,6]. The state of the art in SOEC for YSZ based cells using Ni-YSZ as the hydrogen electrode and LSM (or LSM-YSZ) as the oxygen electrode has been relatively active in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have focused on using carbon-containing agents at the anode of a solid oxide electrolysis cell (SOE) to reduce anode oxygen activity, and several studies have demonstrated the use of methane, carbon monoxide, and high surface area carbons at the anode of an electrolyzer to assist in decomposing water into hydrogen and oxygen. [16][17][18][19][20][21] The viability of solid oxide fuel cells utilizing solid carbon or syngas as a primary fuel source has been demonstrated further in a series of recent modeling studies. In one such study, Liu et al modeled the reaction of spherical carbon fuel particles in a molten salt in the anode chamber.…”
Section: Hydrogen and Electricity Production In A Carbon Fuel Cellmentioning
confidence: 99%
“…The performance of various anodes was then tested by Wang et al in a SOEC for the conditions where the anode was exposed to the reducing gases H2, CH4 and CO. Pd-C-CeO2-YSZ showed the highest catalytic activity and gave the largest reductions in the OCV of the SOE cell. [5] And direct oxidation of methane dominates and resulting in a higher ASR at low CH4 conversions. [6] At system level, analysis of Martinez-Frias et al…”
Section: Introductionmentioning
confidence: 99%